A case of facial vein rupture induced by coughing - Hyakusoku, Hiroshi; Furukawa, Shun; Aoyama, Jun; Nakayama, Meijin (Brazilian Journal of Case Reports, 2024)
Peritonsillar abscess, deep neck infection, epiglottitis, laryngeal edema, and upper airway foreign bodies are frequently encountered emergencies in otolaryngology wards. In contrast, spontaneous vascular rupture in the neck is rare. A 57-year-old man visited our hospital with left neck pain and sudden onset of submandibular neck swelling after coughing. Contrast-enhanced computed tomography revealed a poorly enhanced mass lesion located at the left upper neck. The most prominent swelling was observed around the facial vein. Exploration of the left mass lesion under general anesthesia was performed. A perforation and gusher were found at the branch of the left common facial vein. The perforation was ligated on both the central and peripheral sides. The rupture of the facial vein was presumed to be idiopathic, possibly caused by coughing. No evidence suggestive of vasculitis syndrome, hereditary predisposition, or symptoms indicating vascular fragility were found. We report the first case report of facial vein rupture possibly induced by coughing with massive swelling on the neck and oral floor. To prevent potential complications, such as airway stenosis due to neck swelling and the risk of hemorrhagic shock, it was necessary to promptly perform imaging diagnostics and surgical intervention to achieve hemostasis and remove the hematoma.